Sosiolek dalam film Uang Panai’ 2 Maha(L)R sebagai sumber belajar kontekstual bahasa Indonesia berbasis kearifan lokal - Anzar, Anzar; Cahyani, Isah; Mulyati, Yeti; Kurniawan, Khaerudin (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to identify and analyze sociolects found in the film Uang Panai’ 2 Maha(L)R and to examine their relevance to Indonesian language learning based on local wisdom. A qualitative descriptive approach was employed, with film dialogues serving as the primary data source, collected through viewing and note-taking techniques. Data were analyzed using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The findings reveal four factors influencing the use of sociolects in the film: speakers’ age, employment status, educational level, and socioeconomic class. Age differences emerge as the most dominant factor, reflected in forms of address and diction that indicate hierarchical relations and politeness in intergenerational interactions. Employment status is characterized by technical vocabulary and professional communication styles, while educational level is marked by the use of formal and academic language. Socioeconomic class is manifested through code-mixing and lexical choices that signal social status. The study concludes that film dialogues can function as contextual learning resources for teaching language variation, linguistic politeness, and local cultural values in Indonesian language education.